2020
DOI: 10.1101/2020.06.19.160341
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid kinetics of lipid second messengers controlled by a cGMP signalling network coordinates apical complex functions inToxoplasmatachyzoites

Abstract: Host cell invasion and subsequent egress by Toxoplasma parasites is regulated by a network of cGMP, cAMP, and calcium signalling proteins. Such eukaryotic signalling networks typically involve lipid second messengers including phosphatidylinositol phosphates (PIPs), diacylglycerol (DAG) and phosphatidic acid (PA). However, the lipid signalling network in Toxoplasma is poorly defined. Here we present lipidomic analysis of a mutant of central flippase/guanylate cyclase TgGC in Toxoplasma, which we show has disru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Phospholipid flipping activity is of great biological importance for the biogenesis of vesicles ( 50 , 51 ), creating a fusion-competent bilayer ( 52 ), maintaining membrane stability ( 53 , 54 ), and generating signaling cues ( 55 57 ). It was recently reported that this particular Toxoplasma P4-flippase localizes to the endoplasmic reticulum ( 58 ), while the HyperLOPIT proteome assigned it to the Golgi-plasma membrane ( 27 ). Dissecting how the flippase SNPs modulate the kinetics or substrate preference will require extensive further work.…”
Section: Discussionmentioning
confidence: 99%
“…Phospholipid flipping activity is of great biological importance for the biogenesis of vesicles ( 50 , 51 ), creating a fusion-competent bilayer ( 52 ), maintaining membrane stability ( 53 , 54 ), and generating signaling cues ( 55 57 ). It was recently reported that this particular Toxoplasma P4-flippase localizes to the endoplasmic reticulum ( 58 ), while the HyperLOPIT proteome assigned it to the Golgi-plasma membrane ( 27 ). Dissecting how the flippase SNPs modulate the kinetics or substrate preference will require extensive further work.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, secretory pathway genes also trend up during evolution (Figure 7a). It was recently reported this particular Toxoplasma P4-flippase localizes to the ER [56], while a whole parasite organelle proteomic approach assigned it to the a dynamic Golgi/PM localization [30]. Dissecting how the flippase SNPs modulate the kinetics or substrate preference will require extensive further work.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, both enzymes can generate cGMP, which activates PKG and a signaling cascade, which includes calcium release and activation of calcium-dependent proteins kinases (CDPKs). The flippase domain of GCs are known to be essential; however, their exact mechanism in the above mentioned process is unclear [ 55 , 84 , 85 ]. In a study that monitored the in vitro virulence traits of a lab-adapted T .…”
Section: Lipid Scavenging Mechanismsmentioning
confidence: 99%